Africana Health Psychology: A Cultural Perspective - Lovett, Marilyn D. (Lexington Books, 2023)
Africana Health Psychology: A Cultural Perspective consists of a discussion of health psychology among populations of African descent throughout the diaspora and includes those living in the US such as Caribbean and continental Africans of color. The focus of this work is on health equity with an emphasis on cultural affirmation as protective factors. This book is unique because it merges Africana/Black psychology and health psychology, endorses a strength-based, rather than a deficits-based model of health among Black people, and describes research consisting solely of African-descended participants. From the first chapter designed to disrupt the narrative to the last chapter offering hope for a brighter day, the reader is asked to suspend all preconceived notions of Black people and health. Research findings from childhood to old age are explored in culturally grounded theoretical frameworks. Resilience and spirituality are key themes throughout this volume, meant to enhance cultural competency for practitioners, scholars, students, community members, and anyone interested in expanding their skill set or leaving their comfort zones.